2000
DOI: 10.1091/mbc.11.10.3509
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of β-Catenin Induces Apoptosis Independent of Its Transactivation Function with LEF-1 or the Involvement of Major G1 Cell Cycle Regulators

Abstract: ␤-Catenin promotes epithelial architecture by forming cell surface complexes with E-cadherin and also interacts with TCF/LEF-1 in the nucleus to control gene expression. By DNA transfection, we overexpressed ␤-catenin and/or LEF-1 in NIH 3T3 fibroblasts, corneal fibroblasts, corneal epithelia, uveal melanoma cells, and several carcinoma cell lines. In all cases (with or without LEF-1), the abundant exogenous ␤-catenin localizes to the nucleus and forms distinct nuclear aggregates that are not associated with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
136
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 39 publications
19
136
3
1
Order By: Relevance
“…26 The role of ␤-catenin in apoptotic regulation appears to be cell-type specific. [27][28][29] In line with our data, upregulation of the ␤-catenin/Tcf-4 signaling pathway has been demonstrated to inhibit apoptosis in fibroblasts. 27 However, recent work has reported that ␤-catenin promotes apoptosis in other cell types.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…26 The role of ␤-catenin in apoptotic regulation appears to be cell-type specific. [27][28][29] In line with our data, upregulation of the ␤-catenin/Tcf-4 signaling pathway has been demonstrated to inhibit apoptosis in fibroblasts. 27 However, recent work has reported that ␤-catenin promotes apoptosis in other cell types.…”
Section: Discussionsupporting
confidence: 89%
“…27 However, recent work has reported that ␤-catenin promotes apoptosis in other cell types. 28,29 The disparity concerning the pro-or antiapoptotic role of ␤-catenin in different cell types is not surprising to the field of vascular biology given that numerous factors, including nitric oxide, glucose, and TGF␤, have opposing effects on vascular endothelial cells compared with VSMCs. 2 Our work demonstrates that the ability of ␤-catenin to promote survival and activate cyclin D1 was mediated through Tcf-4.…”
Section: Discussionmentioning
confidence: 99%
“…However, a proapoptotic role of HGF (Arakaki et al, 1998;Matteucci et al, 2003;Rasola et al, 2004) and b-catenin (Kim et al, 2000;van Gijn et al, 2001;Edlund et al, 2005) was also reported in several models. Here, we show that the HGFR transduction axis and the b-catenin/TCF pathway cooperate in underpinning survival signals, whose importance probably increases during carcinoma progression.…”
Section: Discussionmentioning
confidence: 98%
“…Kim et al reported that overexpression of ␤-catenin induced apoptosis independent of its transactivation function or the involvement of G1 cell cycle regulators. 29 They transfected NIH 3T3 cells as well as tumor cell lines (colon carcinomas, an ovarian tumor, and a uveal melanoma) with wild-type ␤-catenin DNA and observed the apoptosis in those cells overexpressing ␤-catenin. Collectively, in NSCLCs, accumulated ␤-catenin in the cytoplasm and/or nucleus with might act favorably to overcome the activation of proliferative signals and thus have no or little oncogenic effect via activation of the Wnt pathway, unlike in colon carcinomas or HCCs.…”
Section: Discussionmentioning
confidence: 99%